The effect of water stress in reproductive stages towards growth of rice plant / Muhammad Firdaus Hasron - Hasron, Muhammad Firdaus (Faculty of Plantation and Agrotechnology, 2018)
Rice or rice (Oryza sativa) is one of the major crops in Malaysia after oil palm and rubber. This study focuses primarily on the effects of water pressure in the breeding growth stage towards rice production. The objective of this study was to identify the effects of water pressure on the rice during the breeding stage and summarize the water pressure relationship within the breeding stage and rice plant. The variety of paddy used was the high yield variation produced by MARDI, MR 219. The experiment was compiled four blocks randomly at greenhouse at Universiti Teknologi Mara (UiTM) Jasin Campus for nine weeks. Each paddy has four treatments such as 0 (4cm), 1 (8cm), 2 (10cm), and 3 (12cm) treatments. For each treatment there are four replicates. Some data on paddy growth rates were recorded for analysis using Minitab software in one direction ANOVA. The results showed that the treatment of 3 (12 cm) had a better result compared with the treatment of 0 (4cm) getting the lowest result. This decision suggests that 12 cm water height can be easily implemented in paddy cultivation by farmers who provide better results for reproductive growth.